Pejuang anti-bullying: Kampanye kebaikan melalui poster dan roleplay di SD Alkhairat 02 Kota Ternate - Eko Purnomo; Bujuna Alhadad; Risna Srinawati; Kodrat Hi Karim; Rosida Marasabessy; Nurhuda Taepon; Dwi W. Nurharyanto; Ridwan Jusuf; Suhardi Abdullah; Samsu Somadayo; Selvi Wulandari; Darmawaty Hadi; Wawan S. Nadra; Ayu A. Akbar; Andi Ramadani; Asri S. Tamalene; Fauzia Harun (Universitas Hamzanwadi, 2026)
Bullying in elementary schools can negatively affect students’ emotional, social, academic, and moral development and contribute to an unsafe school environment. This community service program aimed to improve students’ understanding of the forms, effects, and prevention of bullying while fostering empathy and the courage to respond to bullying incidents. The program was conducted at SD Alkhairat 02 Kota Ternate using a participatory-educational approach that combined interactive presentations, discussions, roleplay, and the creation of kindness campaign posters. The roleplay involved students taking the roles of perpetrators, victims, and bystanders to help them understand bullying situations and appropriate responses through the 3L approach (Lawan, Lari, Lapor—Resist, Leave, Report). Evaluation was conducted qualitatively through participatory observation during the activities, documentation of student posters, and observation of students’ responses and participation. The results showed that students began to distinguish between joking and bullying after participating in the roleplay activities. Students also demonstrated empathy toward victims and showed courage in helping their peers and reporting bullying incidents to teachers. They actively participated in creating and presenting kindness campaign posters. The activity concluded with a joint commitment declaration as “Pejuang Kebaikan” (Kindness Champions). These findings suggest that combining posters and roleplay can provide a relevant educational approach for introducing bullying prevention to elementary school students. Continued involvement of teachers, parents, and school policies is needed to support the consistent application of anti-bullying values.